Small daily doses of orange heirloom (“Moonglow”) tomatoes dose-dependently increase plasma and liver lycopene concentrations in rats - Walallawita US; Wolber FM; Ziv-Gal A; Kruger MC; Heyes JA; Walallawita Kankanamge U (Oxford University Press on behalf of Japan Society for Bioscience, Biotechnology, and Agrochemistry, 2025)
Lycopene in red tomatoes is mainly in the poorly bioavailable all-trans- isomeric form, while “Moonglow,” an orange heirloom tomato, contains more bioavailable cis-lycopene isomers. Consuming around 1.5 kg of red tomatoes daily is needed to achieve effective plasma lycopene levels (>0.45 µmol/L). This study hypothesized that small daily doses of “Moonglow” tomatoes could achieve beneficial lycopene levels in rats. Female Sprague-Dawley rats were supplemented with “Moonglow” tomato powder. In Study 1, rats received lycopene at 0, 0.05, 0.35, or 2.6 mg/kg body weight daily for five days. Plasma and liver lycopene concentrations increased dose-dependently. In Study 2, rats given 0.35 mg/kg daily showed dose- and time-dependent increases in lycopene. Plasma lycopene reached 0.42 µmol/L after 4 days, similar to beneficial human levels. These findings suggest that a reasonable daily intake of “Moonglow” tomatoes can achieve effective plasma lycopene concentrations.